2018
DOI: 10.1177/1471301218816246
|View full text |Cite
|
Sign up to set email alerts
|

Exercise physiology in aged care: Perceptions and acceptability from the perspectives of family members and care staff in the residential aged care environment

Abstract: As we age, maintaining physical functionality is important with respect to wellbeing and healthy ageing. For older adults with dementia this may be difficult, particularly in the residential aged care environment. This article reports the qualitative examination of an Exercise Physiologist-delivered exercise programme for residents with dementia. Perspectives related to the perceived impact and acceptability of the programme, as well as barriers to implementation, and delivery of exercise to residents, were so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Such programs have been well received, and family members and care staff have reported positive outcomes in mood, social participation and pro-social behaviour. 21 We found that the program implementation is cost-effective, if maintenance (of equipment) and (staff) training-related costs were not accounted for. However, if these costs were included in the cost evaluation, and the program was designed in a way that the cost per participant could be kept under A$100 (while maintaining the QoL outcome), the program would maintain its cost-effectiveness (Table 3, lines 'C').…”
Section: Discussionmentioning
confidence: 87%
“…Such programs have been well received, and family members and care staff have reported positive outcomes in mood, social participation and pro-social behaviour. 21 We found that the program implementation is cost-effective, if maintenance (of equipment) and (staff) training-related costs were not accounted for. However, if these costs were included in the cost evaluation, and the program was designed in a way that the cost per participant could be kept under A$100 (while maintaining the QoL outcome), the program would maintain its cost-effectiveness (Table 3, lines 'C').…”
Section: Discussionmentioning
confidence: 87%
“…The importance of Physical activity are many as it diminishes the risk of various non-communicable and chronic health conditions, which includes heart disease, hypertension, type 2 diabetes, colon, post-menopausal breast and endometrial cancers, stroke, osteoporosis, osteoarthritis, depression, falls and disability in the elderly people 12,14,16,17,19,[21][22][23][24]26,[30][31][32][33][34][35][36][37][38] . From the extant review, it is therefore concluded that physical activities have numerous advantages for the prevention and management of many health-related conditions been faced by the elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the effect of 6 months of aerobic training on adipokines as breast cancer risk factors in postmenopausal women revealed that exercise programs can be considered as an effective behavioral modification in breast cancer prevention 25 . Also, for improved functional ability in elderly people with dementia, a person-centered exercise approach, delivered by an expert is effective 26 .…”
Section: Benefits Of Physical Activity To the Health Of An Elderly Pementioning
confidence: 99%
“…For the survey questions, please see Supporting Information. Partners‐in‐care were also involved in semi‐structured interviews designed to explore perceptions around the program further; these findings are reported elsewhere …”
Section: Methodsmentioning
confidence: 99%